Approaches to palliative oxygen therapy in chronic obstructive pulmonary disease: a multi‐national survey of specialists. Issue 2 (12th February 2019) - Smallwood, Natasha; Currow, David; Booth, Sara; Spathis, Anna; Irving, Louis; Philip, Jennifer
Abstract: As palliative oxygen therapy (POT) is beneficial only to a minority of patients with chronic breathlessness, it is no longer routinely recommended. This multi‐national, online survey of respiratory and palliative medicine specialists, with 440 participants, identified that prescription of POT has decreased over the past decade; however a sizeable proportion of doctors, particularly within palliative care, still support and recommend POT. Further education and research regarding the optimal management of chronic breathlessness are required.